2004
DOI: 10.1093/molehr/gah081
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization and expression of urokinase plasminogen activator (uPA), its receptor (uPAR), and its inhibitor (PAI-1) mRNA and protein in endometrial tissue during the menstrual cycle

Abstract: Normal endometrium is a highly dynamic tissue, which responds to ovarian steroids with cyclic proliferation, differentiation (secretion), and degradation (menstruation). The urokinase plasminogen activator (uPA)-dependent proteolytic cascade as well as ligand activation of the uPA receptor (uPAR) is critically involved in physiological as well as pathophysiological aspects of tissue expansion and remodelling. Cyclic variation and distribution of uPA, uPAR and plasminogen activator inhibitor 1 (PAI-1) mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…13 The present DNA microarray data confirm differential expression of many genes that had been previously identified to be changed during decidualization. For example, prolactin 13 and PAI-1 20 have been shown to be increased in response to estrogen plus progesterone; our data confirm these findings. In contrast, E alone did not stimulate a phenotypic change in T-HESCs and few genes showed significant changes in expression in response to E alone.…”
Section: Discussionsupporting
confidence: 88%
“…13 The present DNA microarray data confirm differential expression of many genes that had been previously identified to be changed during decidualization. For example, prolactin 13 and PAI-1 20 have been shown to be increased in response to estrogen plus progesterone; our data confirm these findings. In contrast, E alone did not stimulate a phenotypic change in T-HESCs and few genes showed significant changes in expression in response to E alone.…”
Section: Discussionsupporting
confidence: 88%
“…26,27 PAI-1 messengerRNA and protein are localized in endometrial epithelium and stromal cells around small blood vessels. 28 SP is thought to play important roles in the …”
Section: Discussionmentioning
confidence: 99%
“…The nature and the regulation of this receptivity in the human are unknown. This Swedish group has recently reported that urokinase plasminogen activator (uPA) mRNA is found in the endometrial stroma whereas uPA protein is located in both stromal and epithelial cells [6] . Similarly, in the secretory phase uPAR mRNA is found in the stroma and uPAR protein in the epithelium [6] .…”
Section: Regulation and Characterisation Of Endometrial Receptivitymentioning
confidence: 99%